2020
DOI: 10.1016/j.ctro.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in primary metastatic site in rectal cancer; associated with hemodynamic factors?

Abstract: Background and purposeWe investigated how features relating to pelvic cavity anatomy and tumor hemodynamic factors may influence systemic failure in rectal cancer.Materials and methodsRectal cancer patients (207 women, 343 men), who had been prospectively enrolled onto six cohorts and given curative-intent therapy, were analyzed for the first metastatic event. In one of the cohorts, the diameter of the inferior mesenteric vein (IMV) was assessed on diagnostic abdominal computed tomography images (n = 113). Tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Interestingly, CXCL7 has been proposed as a circulating biomarker for CRC detection [ 46 ]. With regard to vascular processes, we recently showed that hemodynamic factors of the rectal cancer differ and result in distinctive outcomes in men and women [ 47 , 48 ]. In our previous vitamin D study, a weak inverse correlation between circulating 25(OH) D and SIR markers appeared in all patients analyzed together [ 13 ]—it might be that stronger and more distinct modes of systemic inflammation with respect to the vitamin D status had been revealed if male and female patients had been analyzed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CXCL7 has been proposed as a circulating biomarker for CRC detection [ 46 ]. With regard to vascular processes, we recently showed that hemodynamic factors of the rectal cancer differ and result in distinctive outcomes in men and women [ 47 , 48 ]. In our previous vitamin D study, a weak inverse correlation between circulating 25(OH) D and SIR markers appeared in all patients analyzed together [ 13 ]—it might be that stronger and more distinct modes of systemic inflammation with respect to the vitamin D status had been revealed if male and female patients had been analyzed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CXCL7 has been proposed as a circulating biomarker for CRC detection [46]. With regard to vascular processes, we recently showed that hemodynamic factors of the rectal cancer differ and result in distinctive outcomes in men and women [47,48]. In our previous vitamin D study, a weak inverse correlation between circulating 25(OH) D and SIR markers appeared in all patients analyzed together [13]-it might be that stronger and more distinct modes of systemic inflammation with respect to the vitamin D status had been revealed if male and female patients had been analyzed separately.…”
Section: Discussionmentioning
confidence: 99%
“…The patient cohorts with demographic data have been detailed in full previously. 19 Briefly, the IC (NCT01816607) consisted of 122 stage I-III patients with a mean age of 64 years, enrolled at Akershus University Hospital (Lørenskog, Norway) between October 28th, 2013 and December 17th, 2017, and was censored on January 2nd, 2020. The study was designed as a prospective biomarker study for patients enrolled according to unselected recruitment.…”
Section: Patients and Proceduresmentioning
confidence: 99%
“…The VC1 was used because 35.4% of the 79 cases had organ-invasive (T4) disease that is at particularly high risk of poor outcome. 18 The VC2 was chosen because 49.6% of the 135 cases had low primary tumour (5 cm or less from the anal verge) with the specific risk of developing lung metastases 19 and therefore might challenge our hypothesis. The VC3 was analysed because its 59 cases resembled those of VC1.…”
Section: Introductionmentioning
confidence: 99%